2011
DOI: 10.1097/cej.0b013e328345f985
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of prospective studies of red meat consumption and colorectal cancer

Abstract: The relationship between red meat consumption and colorectal cancer (CRC) has been the subject of scientific debate. To estimate the summary association between red meat intake and CRC and to examine sources of heterogeneity, a meta-analysis of prospective studies was conducted. Thirty-four prospective studies of red meat and CRC were identified, of which 25 represented independent nonoverlapping study populations. Summary relative risk estimates (SRREs) for high versus low intake and dose-response relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 55 publications
1
72
0
5
Order By: Relevance
“…Within this diet, olive oil appears to reduce breast cancer risk specifically (Tsuji et al, 2012). Other aspects of the 'Mediterranean diet' have beneficial properties and may protect against other types of cancer, but are discussed thoroughly in other reviews (Egeberg et al, 2009;Taylor et al, 2009;Kabat et al, 2010;Alexander et al, 2011;Fortes and Boffetta, 2011;Fu et al, 2011;Hardy and Tollefsbol, 2011;Hauner et al, 2011;Jansen et al, 2011;Shanmugam et al, 2011;Magalhaes et al, 2012).…”
Section: Monounsaturated Fats and Olive Oilmentioning
confidence: 99%
“…Within this diet, olive oil appears to reduce breast cancer risk specifically (Tsuji et al, 2012). Other aspects of the 'Mediterranean diet' have beneficial properties and may protect against other types of cancer, but are discussed thoroughly in other reviews (Egeberg et al, 2009;Taylor et al, 2009;Kabat et al, 2010;Alexander et al, 2011;Fortes and Boffetta, 2011;Fu et al, 2011;Hardy and Tollefsbol, 2011;Hauner et al, 2011;Jansen et al, 2011;Shanmugam et al, 2011;Magalhaes et al, 2012).…”
Section: Monounsaturated Fats and Olive Oilmentioning
confidence: 99%
“…In cancer, a high consumption of carbohydrate-rich foods, such as fruit, vegetables and whole grain, has been associated with a reduced risk of many types of cancer, 13 whereas high consumption of meat, especially red or processed meat, may increase the risk of colorectal cancer. 13,14 In a recent American observational study, an increased risk of diabetes was seen in men with a lower intake of carbohydrates and a higher intake of animal protein and fat over a period of 20 years, 15 but a similar study in women showed no increased risk. 16 More conclusive evidence is needed.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most studies [3][4][5] have investigated the effect of specific foods, food groups, or nutrients. Consumption of vegetables and dairy products has been related to a decreased colorectal cancer risk, whereas consumption of red and processed meat has been associated with an increased Risk.…”
Section: Introductionmentioning
confidence: 99%